Listening to Immokalee moms: How stages of change theory guided the discovery of healthy eating messages to Latino mothers. Issue 2 (5th June 2017) - Morton, Cynthia; Galindo, Sebastian; Morera, Maria; Dodoo, Naa; Gonzalez, Cristobal; Wu, Linwan; Fundingsland, Suzanne; Auguste, Kendra; Headrick, Lauren; Monaghan, Paul; Shelnutt, Karla
Abstract : Purpose: The purpose of this paper is to present a case study of the research steps taken to identify message directions for a community-wide health communication campaign aimed at supporting healthier eating behaviors among Latino farmworker families in the Immokalee community in Florida. Latino mothers were targeted to understand their beliefs about children's healthy eating needs and identify communication campaign opportunities that would reinforce choices made in the home, surrounding meal planning, food selection and preparation and portion sizes. Design/methodology/approach: A sequential mixed-methods approach using focus group, group interview and qualitative message concept testing was used in three distinct stages of research exploration. An independent sample was recruited at each stage through convenience sampling and snowball sampling methods. The stages of change theory provided a framework for research inquiry in the context of healthy eating-at-home practices. Findings: In general, mothers were aware and participatory in the effort to serve healthy meals for their children at home. The time and money associated with buying nutritious foods and cooking healthy meals daily was stressful, but they were receptive to communication efforts to help them maintain their commitment to give their children healthy foods. These findings provided directional opportunities for the discovery and implementation of health communication strategies. Test results found that the target was most receptive to message strategies that acknowledged the responsibility of both parents to model healthy eating practices to children. Research limitations/implications: Recruiting resulted in small sample sizes at each stage of the investigation. The reliability of quantitative measurement was a limitation to the research conclusions. Practical implications: Partnership with the audience from discovery to conceptualization resulted in messages that uniquely resonated with the audience for which they were aimed. Understanding about the target stage of readiness improves message effectiveness to the target group. Social implications: Health communication campaigns planned and developed with the target audience at its center will generate message strategies that effectively address issues of greatest relevance to those communication agents that seek to change. Originality/value: The study provides a unique exploration of the steps that health communication agents should pursue to establish a thorough profile of their target audience and the issues that resonate when considering healthy eating behavior at home. The application of the stages of the change model encouraged the discovery of issues surrounding the challenge and highlighted potential obstacles that would mitigate the behavior change efforts.